Markers of atherosclerosis lipoprotein-associated phospholipase A2 and E-selectin and vascular risk factors in patients with carotid stenosis - Dubenko, Olga; Anysienkova, Victoria (ScienceRise: Medical Science, 2021)
The aim of this study is to evaluate serum level biomarkers of atherosclerosis lipoprotein-associated phospholipase A2 and E-selectin in patients with atherosclerotic carotid stenosis with different clinical manifestation in associated with vascular risk factors. Materials and methods: A total 106 patients with atherosclerotic carotid stenosis (74 men and 32 women, aged from 31 to 74 years, mean 62.6±0.9) were included: with acute ipsilateral atherothrombotic stroke (35), history of stroke and carotid endarterectomy (41) and 30 patients with asymptomatic carotid stenosis. The control group consist of 20 health subjects without cardiovascular disease. All participants underwent duplex sonography. Lipoprotein-associated phospholipase A2 and E-selectin was measured using commercially available (ELISA) kit. Results: The level of lipoprotein-associated phospholipase A2 was in general 55.664±3.537 ng/ml, which was significantly higher (M-W U=10, p=1.023136´10-11 <0.05) than in the control group (9.296±0.935 ng/ml). Level was significantly higher in groups of symptomatic patients who underwent carotid endarterectomy (p=0.04893), and proportion patients with high degree stenosis >70 % was greater in this group. The level of E-selectin in the study patients was significantly higher (7.653±0.246 pg/ml) than in the control group (3.101±0.503 pg/ml) p<0.05. No association the serum level of lipoprotein-associated phospholipase A2 and E-selectin with common stroke risk factor such as hypercholesterinemia, smoking and body mass index were found, but positive correlation of lipoprotein-associated phospholipase A2 with E-selectin was significant (p=0.00085). Conclusions: Increasing plasma level lipoprotein-associated phospholipase A2 and E-selectin in patients with the carotid atherosclerotic stenosis were observe. Statistically significant correlation between the level of lipoprotein-associated phospholipase A2 and E-selectin were found in symptomatic carotid atherosclerotic stenosis